The Role of Mosques in Improving the Quality of Religious Education in Urban Communities - Rahayu, Herlis Wulan Sari (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study explores the role of mosques in enhancing the quality of religious education within urban communities. Given the rapid urbanization and the resulting shifts in cultural and social dynamics, the mosque has emerged as a critical center for religious learning and community engagement. Utilizing a qualitative approach through a literature review and library research, this paper investigates how mosques contribute to religious education, focusing on their programs, community outreach, and the adaptation of teaching methods in urban settings. It examines various aspects, such as the mosque's role in offering supplementary religious education for children and adults, fostering intergenerational dialogue, and serving as a space for spiritual guidance and moral development. The study also considers the challenges faced by urban mosques, such as limited resources and the diverse needs of a rapidly changing demographic. By reviewing existing literature, this research aims to provide insights into the effective strategies employed by mosques in improving the religious education quality in urban areas. The findings suggest that mosques play an essential role in bridging educational gaps, offering a platform for lifelong learning, and nurturing community cohesion. In conclusion, the mosque's role in urban religious education remains significant, and further support and development of its educational initiatives are crucial for fostering a spiritually grounded urban society.